Beowulf, a hero's tale retold - Rumford, James, 1948- (Houghton Mifflin Co., 2007)
A simplified and illustrated retelling of the exploits of the Anglo-Saxon warrior, Beowulf, and how he came to defeat the monster Grendel, Grendel's mother, and a dragon that threatened the kingdom.